Mental Training Models in Physical Education, Sports and Health Subjects for Volleyball in Elementary School Students - Yuni Astuti; Bekir Erhan Orhan; Erianti Erianti; Sameer Badri Al-Mhanna; Alexios Batrakoulis (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The association between mental and physical fitness is critical for young people participating in physical education and sports activities. However, current evidence shows that elementary schools need a mental training learning model and a course of play strategies for volleyball material. Therefore, it is necessary to design a particular model of mental training learning and a course of play strategy on volleyball material for elementary school students. The objective of the present study was to produce a model that meets valid, practical, and effective criteria for elementary school students using the Borg and Gall model. Observation, questionnaires, and tests were used to collect data from 22 elementary school students 10–11 years old. A mental training learning model and a course of play strategies were generated to meet the valid criteria, practical category, and effective criteria to be applied to volleyball material in elementary schools and to positively impact improving basic movement abilities and basic techniques of students' volleyball games. Results showed that elementary school students' basic movement abilities in volleyball were more efficient after using the mental training model and a course of play strategy than without using it. Such an outcome highlights the importance of implementing exercise imagery to lead to more engaging and effective school-based physical activity interventions.